A present for Freddie Small - Butterworth, Nick.; Evans, Michael, 1966- (London : Egmont, 2007)
Freddie Small's parents do not know what to do to get him to go to bed peacefully, but his grandmother has some very good ideas.
2.9
K-3
Keywords: Bedtime -- Juvenile fiction; Gifts -- Juvenile fiction; Grandmothers -- Juvenile fiction; Parent and child -- Juvenile fiction; Bedtime -- Fiction; Gifts -- Fiction; Grandmothers -- Fiction; Parents -- Fiction; Bedtime -- Fiction; Gifts -- Fiction; Grandmothers -- Fiction; Parent-child relationship -- Fiction